Method of Syntactic Analysis of Chinese Sentences on Topical Components - Kotcik, K. E. (Nauc̆nyj dialog (Online), 2018)
The article is devoted to the syntactic analysis of sentences of isolating languages (Chinese), to the study of possible ways of such analysis based on various linguistic concepts, to the search for the most optimal variants. The relevance of the study is determined by the fact that the topic strategy naturally becomes one of the leading in the analysis of Chinese language material. The novelty of the work is seen in the fact that the question of the method of application of the strategy / statements of the predication concept of language in practice remains open: in the preparation of educational materials, processing of grammars and their details. The article provides an overview of the methods of syntactic analysis of the constructions in the languages of the isolating type. The algorithms of the analysis of sentences of the Chinese language on topical components are proposed. The author’s development of syntactic analysis of predication chains with the use of graphical method is presented. The author emphasizes that the identification and classification of topic structures is a scientifically sound and practically verifiable (subject to further expansion) analysis strategy that most fully reflects the typology and realities of the Chinese language. The question is raised about the possibility of creating a holistic, systematic and self-sufficient method of syntactic analysis without relying on the concept of European grammatical tradition.